Angiotensin II–Mediated Left Ventricular Abnormalities in Chronic Kidney Disease. (1st June 2012) - Raizada, Veena; Hillerson, Dustin; Amaram, Jaya Sheela; Skipper, Betty
Abstract : Angiotensin II (ATII), the biologically active product of the renin-angiotensin system (RAS), is involved in modulation of left ventricular (LV) structure and function in chronic kidney disease (CKD). Because the RAS system is overactive in CKD, excess ATII accumulates in the heart, thereby promoting myocyte hypertrophy, fibroblast proliferation, interstitial accumulation of collagen, and microvessel disease. These cardiac abnormalities are further enhanced by a possible interaction between enhanced RAS activity and hypercalcemia, hyperphosphatemia and secondary hyperparathyroidism, and vitamin D deficiency. The ATII-associated stimulation of aldosterone production from the adrenal gland and the increase in activity of the sympathetic system in CKD, further contribute to LV abnormalities. Myocardial structural changes are major determinants of an increase in myocardial stiffness, leading to LV diastolic and systolic function impairment, and clinical congestive heart failure. Other complications include cardiac conduction disturbances, QT prolongation, and arrhythmias, which all contribute to elevated cardiovascular mortality in patients with CKD.